2019
DOI: 10.1051/0004-6361/201936764
|View full text |Cite
|
Sign up to set email alerts
|

VLT/SPHERE exploration of the young multiplanetary system PDS70

Abstract: Context. PDS 70 is a young (5.4 Myr), nearby (∼113 pc) star hosting a known transition disk with a large gap. Recent observations with SPHERE and NACO in the near-infrared (NIR) allowed us to detect a planetary mass companion, PDS 70 b, within the disk cavity. Moreover, observations in H α with MagAO and MUSE revealed emission associated to PDS 70 b and to another new companion candidate, PDS 70 c, at a larger separation from the star. PDS 70 is the only multiple planetary system at its formation stage detecte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(105 citation statements)
references
References 62 publications
9
92
0
Order By: Relevance
“…This second source is very close to an extended disc feature, consequently its photometry should be done with caution. In Mesa et al (2019), the planetary nature of this companion has been confirmed, and absolute magnitudes in J-, H-, and K-bands could be inferred for two SPHERE epochs. The spectrum in the J-band is very faint, and indistinguishable from the adjacent disc feature, thus the J-band magnitude should be regarded as upper limit.…”
Section: Pds70mentioning
confidence: 72%
See 1 more Smart Citation
“…This second source is very close to an extended disc feature, consequently its photometry should be done with caution. In Mesa et al (2019), the planetary nature of this companion has been confirmed, and absolute magnitudes in J-, H-, and K-bands could be inferred for two SPHERE epochs. The spectrum in the J-band is very faint, and indistinguishable from the adjacent disc feature, thus the J-band magnitude should be regarded as upper limit.…”
Section: Pds70mentioning
confidence: 72%
“…The NaCo Lband map detected emission that is partly covered by the disc, therefore its L-band magnitude should also be taken as an upper limit. Using various atmospheric models, Mesa et al (2019) constrained the mass PDS 70c to be between 1.9 and 4.4 M J .…”
Section: Pds70mentioning
confidence: 99%
“…The planetary mass is commonly estimated by comparing photometric and spectroscopic observations with planetary evolution and atmospheric models (e.g., Müller et al 2018;Keppler et al 2018;Christiaens et al 2019a;Haffert et al 2019;Mesa et al 2019). On the other hand, our method based on the accretion shock model can estimate a dynamic planetary mass (Aoyama & Ikoma 2019).…”
Section: Planetary Massmentioning
confidence: 99%
“…Additionally, albedo of dusty molecular gas is ∼ 0.5 in the optical/NIR wavelengths (Woitke et al 2019), implying that a significant fraction of the stellar luminosity incident onto the protoplanets could be reflected and hence be observable. Emission from several cold clumps of unknown nature with AU-scale sizes at distance of tens of AU from the host star has been recently detected in PDS 70 (Mesa et al 2019), which is one of the objects included in our study. Additionally, if the disruption process is less abrupt than we assumed here then the clumps may be surrounded by emission elongated mainly along their orbits of both gas and dust that could stand out much better than point-like pre-disruption protoplanets.…”
Section: Direct Observational Tests Of the Td Secondary Disc Scenariomentioning
confidence: 99%